Diagnostic aids: the Surgical Sieve revisited. (30th June 2016) - Chai, Jason; Evans, Lloyd; Hughes, Tom
Summary: Background: Diagnostic errors are well documented in the literature and emphasise the need to teach diagnostic skills at an early stage in medical school to create effective and safe clinicians. Hence, there may be a place for diagnostic aids (such as the Surgical Sieve) that provide a framework for generating ideas about diagnoses. With repeated use of the Surgical Sieve in teaching sessions with students, and prompted by the traditional handheld wheels used in antenatal clinics, we developed the Compass Medicine, a handheld diagnostic wheel comprising three concentric discs attached at the centre. We report a preliminary study comparing the Surgical Sieve and the Compass Medicine in generating differential diagnoses. Methods: A total of 48 third‐year medical students from Cardiff University participated in a study aimed at measuring the efficacy of diagnostic aids (Surgical Sieve and Compass Medicine) in generating diagnoses. We quantified the effect each aid had on the number of diagnoses generated, and compared the size of the effect between the two diagnostic aids. There may be a place for diagnostic aids that provide a framework for generating ideas about diagnoses Results: The study suggests that both diagnostic aids prompted users to generate a greater number of diagnoses, but there was no significant difference in the size of effect between the two diagnostic aids. Discussion: We hope that our study with diagnostic aids will encourage the use of robust tools to teach medical students an easily visualised framework for diagnostic thinking.